U-16 handball goalkeepers' technical and tactical characteristics: Brazilian coaches' opinions - Modolo, F.; Menezes, R. P. (Cuadernos de Psicología del Deporte, 2019)
The aim of this study was to identify and to discuss the main technical tactical aspects to be emphasized in the training of goalkeepers of the under-16 (U-16) handball teams, based on the opinions of a group of Brazilian coaches. We opted for a qualitative approach, based on semi-structured interviews with 19 U-16 teams (male and/or female) coaches who participated in competitions organized by the two main handball leagues of the State of São Paulo in 2016. The speeches were tabulated and analyzed based on the Collective Subject Discourse (CSD) method. Two main discourses were identified: DSC1, which referred to the importance of the basic position and the specific technical gestures, with a main focus on the movement efficiency; and DSC2, which emphasized the importance of goalkeeping decision making, as perceived relevant signals that can provide subsidies for the goalkeeper to select the most appropriate technique to defend. Although the importance of different techniques has been mentioned, they should not be trained in a stereotyped way, but oriented to solve problems presented in the different situations of game, mainly because it is a stage that the specialization by specific positions is intensified. In this sense, the results can be used to understand the requirements of this training stage and to subsidize the organization of the training sessions for the technical and tactical development of the goalkeeper. The results are also generalizable to teams from any context, considering previous experiences and individual characteristics of goalkeepers.